The Transformation of Muhammadiyah School Education Through Values-Based Leadership and the Association Ecosystem: A Model of Sustainable Competitive Advantage Through Community Trust Mediation - Fadillah Sabri; Iswan Iswan; Dirgantara Wicaksono (Sahabat Publikasi, 2026)
This research examines the effects of principal leadership (X?), the Superior Program of the Prophet’s Daily 7 Sunnahs (X?), and support from the Muhammadiyah Regional Leadership/PDM (X?) on schools’ sustained competitive advantage (Z), with public trust (Y) as a mediator, at SMA Muhammadiyah Toboali, South Bangka Regency. The research employed an explanatory survey design with 370 respondents and analyzed the data using SEM-PLS (SmartPLS 4.0) with 5,000-subsample bootstrapping. The results show that all direct effects of X?, X?, and X? on Y and Z, as well as the effect of Y on Z, are positive and significant. Mediation analysis further confirms that Y partially mediates the relationships between X?, X?, and X? and Z; therefore, all research hypotheses are supported. The model demonstrates strong explanatory power for variations in public trust and sustained competitive advantage and indicates good predictive relevance. The findings emphasize that Muhammadiyah schools’ competitiveness is strengthened by values-based leadership, the institutionalization of religious habituation as a strategic capability, and organizational support from the Muhammadiyah association that builds public trust. Practically, schools should strengthen integrative leadership, ensure the consistent implementation of the 7 Sunnahs program as an organizational culture, enhance governance synergy with PDM, and systematically manage public communication and engagement to reinforce trust as a lever for sustained competitiveness.